Rethinking the Internationalization of Higher Education as a Transformational Educational Endeavor - Leask, Betty (International Higher Education, 2025)
<h3 id="in-todays-interconnected-and-fragile-world-the-values-that-have-traditionally-driven-the-internationalization-of-higher-education-iohe-are-more-important-than-ever-before-this-paper-argues-that-for-iohe-to-deliver-on-its-promise-it-is-critical-that-we-rethink-it-as-a-transformational-educational-endeavor-for-all-students-practical-strategies-and-a-preliminary-research-agenda-to-support-this-are-provided" data-pm-slice="1 1 []">In today’s interconnected and fragile world, the values that have traditionally driven the internationalization of higher education (IoHE) are more important than ever before. This paper argues that, for IoHE to deliver on its promise, it is critical that we rethink it as a transformational educational endeavor for all students. Practical strategies and a preliminary research agenda to support this are provided.